The α2δ-1-NMDA receptor complex and its potential as a therapeutic target for ischemic stroke - Wu, Tao; Chen, Shao-Rui; Pan, Hui-Lin; Luo, Yi (Frontiers in Neurology, 2023)
N-methyl-D-aspartate receptors (NMDARs) play a critical role in excitotoxicity caused by ischemic stroke, but NMDAR antagonists have failed to be translated into clinical practice for treating stroke patients. Recent studies suggest that targeting the specific protein–protein interactions that regulate NMDARs may be an effective strategy to reduce excitotoxicity associated with brain ischemia. α2δ-1 (encoded by the Cacna2d1 gene), previously known as a subunit of voltage-gated calcium channels, is a binding protein of gabapentinoids used clinically for treating chronic neuropathic pain and epilepsy. Recent studies indicate that α2δ-1 is an interacting protein of NMDARs and can promote synaptic trafficking and hyperactivity of NMDARs in neuropathic pain conditions. In this review, we highlight the newly identified roles of α2δ-1-mediated NMDAR activity in the gabapentinoid effects and NMDAR excitotoxicity during brain ischemia as well as targeting α2δ-1-bound NMDARs as a potential treatment for ischemic stroke.